Strengthening Economic Growth Through Islamic Insurance in Indonesia - Anugrah, Alwarda; Samita, Samita; B, Fadilah Y.; Tenriwaru, Tenriwaru (Contemporary Journal on Business and Accounting, 2024)
Purpose – The purpose of this research is to analyze how Islamic insurance can drive economic growth Design/methodology/approach – The method used is a literature review, involving library research and documentation from academic studies, scientific journals, and written reports on economic growth and Islamic insurance Findings – The findings show that Islamic insurance plays a significant role in economic growth by supporting national development, reducing poverty, and mitigating financial risks from unforeseen events Originality – This research examines the specific contributions of Islamic insurance to economic growth, focusing on its role in financing development, reducing poverty, and mitigating financial risks Keywords: Economic Growth, Islamic Insurance Paper Type Research Result